Upregulation of AMPA receptor GluR2 (GluA2) subunits in subcortical ischemic vascular dementia is repressed in the presence of Alzheimer's disease - Mohamed, Nur-Ezan (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
10.1016/j.neuint.2011.03.010